2008
DOI: 10.1002/ar.20708
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1 Expression is Regulated by TGFβ3 and ALK2 During Valvuloseptal Endocardial Cushion Formation

Abstract: During early heart development at the looped heart stage, endothelial cells in the outflow tract and atrioventricular (AV) regions transform into mesenchyme to generate endocardial cushion tissue. This endocardial epithelial-mesenchymal transition (EMT) is regulated by several regulatory pathways, including the transforming growth factor-beta (TGFb), bone morphogenetic protein (BMP), and Rho-ROCK pathways. Here, we investigated the spatiotemporal expression pattern of ROCK1 mRNA during EMT in chick and examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…During early heart development, endothelial cells in the outflow tract and atrioventricular regions transform into mesenchyme that ultimately becomes endocardial cushion tissue. ROCK1 plays an important role in the regulation of endocardial cell differentiation and migration (Zhao and Rivkees 2004; Sakabe et al 2006) Specifically, ROCK1 is up-regulated at the onset of the epithelial-mesenchyme transition phase in the heart (Sakabe et al 2008). The fact that ROCK1 is up-regulated in both trisomies 18 and 21, and that both valvular and endocardial cushion abnormalities are found in these conditions, is intriguing and suggests a common mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…During early heart development, endothelial cells in the outflow tract and atrioventricular regions transform into mesenchyme that ultimately becomes endocardial cushion tissue. ROCK1 plays an important role in the regulation of endocardial cell differentiation and migration (Zhao and Rivkees 2004; Sakabe et al 2006) Specifically, ROCK1 is up-regulated at the onset of the epithelial-mesenchyme transition phase in the heart (Sakabe et al 2008). The fact that ROCK1 is up-regulated in both trisomies 18 and 21, and that both valvular and endocardial cushion abnormalities are found in these conditions, is intriguing and suggests a common mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…We posit that SNRK’s involvement in the two signaling pathways may not be mutually exclusive since both have been implicated in CMs function previously. For example, TGF-β3 and ALK2 regulate ROCK1 expression during valvuloseptal endocardial cushion formation 38 , and up regulation of bone morphogenetic protein-2 (BMP-2), antagonized TGF-β1/ROCK-enhanced cardiac fibrotic signal through activation of Smurf1/Smad6 complex 37 . In this study, we only focused on ROCK because of the overwhelming evidence suggesting ROCK as a cardiovascular risk factor 39 , and its role in cardiovascular physiology and pathophysiology 4 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that ROCK1/2 is expressed in gastrulating cells (Sakata et al. 2007), and TGF‐β signal is able to upregulate the expression of ROCK1 in endocardial cells at the onset of epithelial‐mesenchymal transition in valvuloseptal endocardial cushion formation (Sakabe et al. 2008).…”
Section: Discussionmentioning
confidence: 99%